Utilization of Hands-On Minds-On Approach toward Achievement in Science - Jomar M Urbano (ASEAN Multidisciplinary Research Journal, 2020)
This study was conducted to test the veracity of Hands-On Minds-On Approach in learning Science. Quasi-Experimental Method was employed using the Randomized Pretest-Posttest Control Group Design among Grade 8 pupils. The results of the pretest of both the experimental and control groups revealed that all the respondents of both groups had low academic performance on the topics of Earth and Space prior to the utilization of the Module showed no significant difference on the level of mastery on such topics. The respondents in the experimental group were taught utilizing the developed and evaluated Module applying Hands-On Minds-On approach while the respondents in the control group were subjected to traditional lecture-discussion method of teaching. The posttest results of the respondents in the experimental group showed significantly higher scores. Respondents’ scored in the posttest were also compared. The respondents in the experimental group obtained higher scores than the respondents in control group. This means that the Module applying Hands-On Minds-On Approach was very effective in increasing the students’ academic performance in Science. It is recommended to develop and evaluate other subject areas applying the said approach.